Activity of the oral mitogen‐activated protein kinase kinase inhibitor trametinib in RAS‐mutant relapsed or refractory myeloid malignancies. Issue 12 (18th March 2016) - Borthakur, Gautam; Popplewell, Leslie; Boyiadzis, Michael; Foran, James; Platzbecker, Uwe; Vey, Norbert; Walter, Roland B.; Olin, Rebecca; Raza, Azra; Giagounidis, Aristoteles; Al‐Kali, Aref; Jabbour, Elias; et al.
Abstract : BACKGROUND: RAS/RAF/mitogen‐activated protein kinase activation is common in myeloid malignancies. Trametinib, a mitogen‐activated protein kinase kinase 1 (MEK1)/MEK2 inhibitor with activity against multiple myeloid cell lines at low nanomolar concentrations, was evaluated for safety and clinical activity in patients with relapsed/refractory leukemias. METHODS: This phase 1/2 study accrued patients with any relapsed/refractory leukemia in phase 1. In phase 2, this study accrued patients with relapsed/refractory acute myeloid leukemia (AML) or high‐risk myelodysplastic syndromes (MDS) with NRAS or KRAS mutations (cohort 1); patients with AML, MDS, or chronic myelomonocytic leukemia (CMML) with a RAS wild‐type mutation or an unknown mutation status (cohort 2); and patients with CMML with an NRAS or KRAS mutation (cohorts 3). RESULTS: The most commonly reported treatment‐related adverse events were diarrhea, rash, nausea, and increased alanine aminotransferase levels. The phase 2 recommended dose for Trametinib was 2 mg orally daily. The overall response rates were 20%, 3%, and 27% for cohorts 1, 2, and 3, respectively, and this indicated preferential activity among RAS ‐mutated myeloid malignancies. Repeated cycles of trametinib were well tolerated with manageable or reversible toxicities; these results were similar to those of other trametinib studies. CONCLUSIONS: The selective, single‐agent activity of trametinib against RAS ‐mutated myeloid malignancies validates its therapeutic potential. Combination strategies based on a better understanding of the hierarchical role of mutations and signaling in myeloid malignancies are likely to improve the response rate and duration. Cancer 2016;122:1871–9 . © 2016 American Cancer Society . Abstract : This is the first study to show a link between RAS ‐mutant myeloid malignancies and clinical responses to mitogen‐activated protein kinase kinase inhibitor therapy. These data highlight the importance of the RAS/RAF/mitogen‐activated protein kinase pathway in leukemogenesis and support further study of trametinib in patients with RAS ‐mutant myeloid malignancies.